2021
DOI: 10.1016/j.ijid.2021.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Puzzling paracoccidioidomycosis: Factors associated with the severity of Paracoccidioides lutzii infections

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…P. venezuelensis is dominant in Venezuela and reported in Colombia as well. P. lutzii is prevalent in central-west Brazil, with scattered cases outside this area [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Epidemiology Of Paracoccidioidomycosismentioning
confidence: 99%
See 1 more Smart Citation
“…P. venezuelensis is dominant in Venezuela and reported in Colombia as well. P. lutzii is prevalent in central-west Brazil, with scattered cases outside this area [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Epidemiology Of Paracoccidioidomycosismentioning
confidence: 99%
“…Recent developments in genetic studies of Paracoccidioides’ different species and their epidemiology show that they co-exist in several regions of Latin America, with a clear overlapping distribution. Interestingly, when the magnitude of gene flow between species was analyzed, Mavengere et al [ 19 ] confirmed that Paracoccidioides species rarely exchange genes despite extensive geographic overlap [ 16 , 17 , 18 , 19 ].…”
Section: Epidemiology Of Paracoccidioidomycosismentioning
confidence: 99%
“…The second and significant group corresponds to the chronic form, found in 80 to 95 % of the total cases, and men between 30 and 50 years of age are the most affected patients ( Nery et al. 2021a , 2021b ). Brazil accounts for up to 80 % of cases of PCM in Latin America, with an incidence of 7.99 cases per 1 000 hospitalizations based on the overall hospital admissions notified to the Ministry of Health in the year 2011 ( Giacomazzi et al.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic species 2 (PS2) was found in Brazil, Venezuela, and Uruguay, while the remaining phylogenetic species PS3 and PS4 appear to be restricted to Colombia and Venezuela, respectively ( Theodoro et al 2012 ). Paracoccidioides lutzii (formerly Pb01-like) is prevalent in central-west Brazil, mainly in Mato Grosso state, with scattered cases outside this area ( Nery et al 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…O crescente desenvolvimento da biologia molecular trouxe novos testes para diagnóstico de PCM, que se baseiam principalmente em PCR e PCR-RFLP. Essas técnicas moleculares ainda estão em busca de melhores alvos que permitam a padronização e aplicação com parâmetros de precisão adequados (Nery, et al, 2021). Higuita-Gutiérrez, et al, (2019) implementação.…”
Section: Discussionunclassified